Variability in Quantity and Quality of Early Linguistic Experience in Children With Cochlear Implants: Evidence from Analysis of Natural Auditory Environments. Issue 2 (March 2022) - Arjmandi, Meisam K.; Houston, Derek; Dilley, Laura C.
Abstract : Objectives: Understanding how quantity and quality of language input vary across children with cochlear implants (CIs) is important for explaining sources of large individual differences in language outcomes of this at-risk pediatric population. Studies have mostly focused either on intervention-related, device-related, and/or patient-related factors, or relied on data from parental reports and laboratory-based speech corpus to unravel factors explaining individual differences in language outcomes among children with CIs. However, little is known about the extent to which children with CIs differ in quantity and quality of language input they experience in their natural linguistic environments. To address this knowledge gap, the present study analyzed the quantity and quality of language input to early-implanted children (age of implantation <23 mo) during the first year after implantation. Design: Day-long Language ENvironment Analysis (LENA) recordings, derived from home environments of 14 early-implanted children, were analyzed to estimate numbers of words per day, type-token ratio (TTR), and mean length of utterance in morphemes (MLUm ) in adults' speech. Properties of language input were analyzed across these three dimensions to examine how input in home environments varied across children with CIs in quantity, defined as number of words, and quality, defined as whether speech was child-directed or overheard. Results: Our per-day estimates demonstrated that children with CIs were highly variable in the number of total words (mean ± SD = 25, 134 ± 9, 267 words) and high-quality child-directed words (mean ± SD = 10, 817 ± 7, 187 words) they experienced in a day in their home environments during the first year after implantation. The results also showed that the patterns of variability across children in quantity and quality of language input changes depending on whether the speech was child-directed or overheard. Children also experienced highly different environments in terms of lexical diversity (as measured by TTR) and morphosyntactic complexity (as measured by MLUm ) of language input. The results demonstrated that children with CIs varied substantially in the quantity and quality of language input experienced in their home environments. More importantly, individual children experienced highly variable amounts of high-quality, child-directed speech, which may drive variability in language outcomes across children with CIs. Conclusions: Analyzing early language input in natural, linguistic environments of children with CIs showed that the quantity and quality of early linguistic input vary substantially across individual children with CIs. This substantial individual variability suggests that the quantity and quality of early linguistic input are potential sources of individual differences in outcomes of children with CIs and warrant further investigation to determine the effects of this variability on outcomes.